In situ measurements of winter wheat diurnal changes in photosynthesis and environmental factors reveal new insight into photosynthesis improvement by super-high-yield cultivation - Ming-yang MA; Yang LIU; Yao-wen ZHANG; Wei-long QIN; Zhi-min WANG; Ying-hua ZHANG; Cong-ming LU; Qing-tao LU (Journal of Integrative Agriculture, 2021)
In past 30 years, the wheat yield per unit area of China has increased by 79%. The super-high-yield (SH) cultivation played an important role in improving the wheat photosynthesis and yield. In order to find the ecophysiological mechanism underneath the high photosynthesis of SH cultivation, in situ diurnal changes in the photosynthetic gas exchange and chlorophyll (Chl) a fluorescence of field-grown wheat plants during the grain-filling stage and environmental factors were investigated. During the late grain-filling stage at 24 days after anthesis (DAA), the diurnal changes in net CO2 assimilation rate were higher under SH treatment than under high-yield (H) treatment. From 8 to 24 DAA, the actual quantum yield of photosystem II (PSII) electron transport in the light-adapted state (ΦPSII) in the flag leaves at noon under SH treatment were significantly higher than those under H treatment. The leaf temperature, soil temperature and soil moisture were better suited for higher rates of leaf photosynthesis under SH treatment than those under H treatment at noon. Such diurnal changes in environmental factors in wheat fields could be one of the mechanisms for the higher biomass and yield under SH cultivation than those under H cultivation. ΦPSII and CO2 exchange rate in wheat flag leaves under SH and H treatments had a linear correlation which could provide new insight to evaluate the wheat photosynthesis performance under different conditions.